Ecuador : Second and Third Reviews Under The Extended Fund Facility Arrangement and Request for a Waiver of Nonobservance and Modifications of Performance Criteria-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Ecuador's Second and Third Reviews Under the Extended Fund Facility Arrangement and Request for a Waiver of NonObservance and Modifications of Performance Criteria. The Ecuadorian authorities have continued to make progress in strengthening the country's fiscal and external positions and have appropriately recalibrated their economic program to include a more moderate fiscal consolidation and international reserves' paths in response to recent developments and to protect pro-poor growth and social spending. Public financial management reforms are paramount to secure fiscal sustainability in the longer term. The reform of the central bank aimed at strengthening central bank autonomy, accountability, and governance will be instrumental in supporting the dollarization regime, boosting reserves, and ensuring their prudent management. Efforts to raise competitiveness should continue to focus on improving transparency, strengthening governance, increasing efficiency of the public sector, and creating conditions in the labor market to facilitate hiring and female participation.